Fibrous substance fluid dispersion, and fiber-reinforced resin composition
By controlling the sedimentation degree of fiber material in the dispersion medium and using thickeners, the problem of uneven dispersion of hydrophobic fibers in the thermoplastic resin is solved, and the stable production of the resin composition and excellent mechanical properties are achieved.
Patent Information
- Application Number
- JP2024189455
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-12
AI Technical Summary
In the prior art, when hydrophobic fiber-reinforced thermoplastic resin is used, aggregates are easily formed in the pipes and pumps, resulting in a clogging of the pipes and unstable resin composition during the manufacturing process, poor mechanical properties, poor water retention, and difficult to disperse uniformly in the resin.
By controlling the sedimentation of fiber materials in the dispersion medium, using a specific proportion of fiber materials and thickeners, ensuring the sedimentation α≤80%, and adding surfactant and dispersion stabilizer to the dispersion medium to improve the dispersion and stability of fibers in the resin.
It effectively prevents the aggregation of fiber materials in the pipes and pumps, ensures the stable production and good dispersion of the resin composition, and improves the mechanical properties and physical stability of the resin.
Smart Images

Figure 2025020229000004 
Figure 2025020229000005 
Figure 2025020229000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a fibrous material dispersion and a resin composition containing a fibrous material. [Background technology]
[0002] Thermoplastic resins are lightweight and have excellent processability, and are therefore widely used in a wide range of applications, including automotive components, electrical and electronic components, office equipment housings, precision parts, etc. However, resins alone often lack sufficient mechanical properties and dimensional stability, and composites of resins and various fibrous materials are generally used.
[0003] In recent years, nanofibers such as cellulose nanofibers (CNF) have come to be used as fibrous materials. Nanofibers such as CNF have the tendency to aggregate in a dry state, so they are produced as aqueous dispersions that enable stable dispersion. [Prior art documents] [Patent documents]
[0004] Patent Document 1 describes an aqueous dispersion that combines highly thickening hydrophilic cellulose fibers with a thickener for the purpose of improving the performance of cosmetics, spray products, etc.; Patent Document 2 describes a thermoplastic resin that contains pulp fibers and a highly absorbent polymer for the purpose of improving the surface gloss of molded bodies recycled from absorbent articles such as disposable diapers; and Patent Documents 3 and 4 describe examples of the combined use of cellulose fibers and a thickener in food and ice packs, respectively.
[0005] [Patent Document 1] JP 2014-141675 A [Patent Document 2] JP 2016-069543 A [Patent Document 3] JP 2013-236585 A [Patent Document 4] JP 2014-133826 A Summary of the Invention [Problem to be solved by the invention]
[0006] In recent years, hydrophobic fibers, including hydrophobically modified CNF, have come to be used as new fiber reinforcements for thermoplastic resins. Hydrophobic fibers have a high affinity with thermoplastic resins, and are therefore expected to have high dispersibility in the resin, greatly improving mechanical properties and dimensional stability.
[0007] Hydrophobic fibers have the tendency to aggregate in a dry state, so they are manufactured as aqueous dispersions that allow for stable dispersion. However, because hydrophobic fibers do not inherently have a high affinity for water, there is an issue that the hydrophobic fiber dispersion is squeezed in narrow flow paths in piping and in gaps formed by the reciprocating motion inside a pump, resulting in the formation of hydrophobic fiber aggregates. Since the compressed aggregates are mainly composed of hydrophobic fibers, there is almost no re-permeation of water, making it difficult to swell and disperse them using water as a medium.
[0008] The hydrophobic fiber agglomerates formed by squeezing not only cause problems in the manufacturing process, such as clogging of pipes and pumps, but also cause problems such as variations in the composition of the resin composition and instability in the density and strength of the resin composition due to the agglomerates being mixed into the resin.
[0009] In addition, a dispersion containing hydrophobic fibers has a problem that it has low water retention and dries in a short time compared to a dispersion containing hydrophilic fibers. As described above, dried agglomerates of hydrophobic fibers are difficult to redisperse in a resin, which leads to poor dispersion in the resin composition and insufficient physical properties.
[0010] The techniques described in Patent Documents 1 to 4 do not address the above-mentioned problems related to the transportability of the dispersion liquid and the mechanical properties of the resin composition.
[0011] The present invention aims to solve the above-mentioned problems specific to slurries containing hydrophobic fibers, and to provide a fibrous material dispersion which, even when hydrophobic fibers are used, results in extremely little generation of agglomerates in piping and / or pumps, thereby enabling stabilization of the production process and good dispersion of the fibrous material in the resin, thereby providing a resin composition with good and stable physical properties. [Means for solving the problem]
[0012] As a result of intensive research into solving the above problems, the present inventors have found that the above problems can be solved by controlling the sedimentation of fibrous materials in a dispersion liquid, and have thus completed the present invention. That is, the present invention includes the following aspects. [1] 100 parts by mass of a dispersion medium; 0.01 to 20 parts by mass of a fibrous material dispersed in the dispersion medium; A fibrous material dispersion comprising: the fibrous material is cellulose fiber, The test dispersion prepared from the fibrous material dispersion had a molecular weight of 1.01 or more, as shown in the following formula (1): α = 1 − ([A] / [B]) (1) (In formula (1), [A] is the height from the bottom of the dispersion to the separation interface, and [B] is the height from the bottom of the dispersion to the top of the dispersion.) The degree of settling α calculated according to the following formula is 80% or less, The test dispersion is the fibrous material dispersion itself when the concentration of the fibrous material in the fibrous material dispersion is 0.05% by mass, and when the concentration is not 0.05% by mass, the test dispersion is a fibrous material dispersion prepared by concentrating the fibrous material dispersion or diluting it with the same dispersion medium as the dispersion medium so that the concentration is 0.05% by mass. [2] The dispersion medium further contains 0.0001 to 2 parts by mass of a thickener relative to 100 parts by mass of the dispersion medium; The fibrous material dispersion according to aspect 1, wherein the fibrous material has a number average fiber diameter of 1 to 1000 nm. [3] The fibrous material dispersion liquid according to claim 2, wherein the thickener is one or more selected from the group consisting of polyacrylamide, polyalkylene oxide, polyacrylic acid and its salts, cellulose derivatives, polyvinyl alcohol, propylene glycol, and alginic acid and its salts. [4] The fibrous material dispersion according to any one of aspects 1 to 3 above, wherein the surface of the fibrous material is hydrophobic. [5] The fibrous material dispersion according to any one of aspects 1 to 4 above, wherein the fibrous material is cellulose nanofibers. [6] The fibrous material dispersion described in claim 5, wherein the cellulose nanofibers have a weight average molecular weight (Mw) of 100,000 or more and a ratio (Mw / Mn) of weight average molecular weight (Mw) to number average molecular weight (Mn) of 6 or less. [7] The fibrous material dispersion according to claim 5 or 6, wherein the cellulose nanofibers have an average alkali-soluble polysaccharide content of 12% by mass or less and a crystallinity of 60% or more. [8] The fibrous material dispersion according to any one of aspects 5 to 7 above, wherein the average acid-insoluble component content of the cellulose nanofibers is 10 mass% or less. [9] The fibrous material dispersion according to any one of the above embodiments 1 to 8, wherein the dispersion medium is water.
[10] A fibrous material dispersion according to any one of aspects 1 to 9 above, comprising a particulate component.
[11] The fibrous material dispersion according to claim 10, which is an emulsion.
[12] A fibrous material dispersion according to any one of aspects 1 to 11 above, comprising a surfactant.
[13] A method for improving the flowability of a fibrous material dispersion containing a dispersion medium and a fibrous material dispersed in the dispersion medium, comprising: The method comprises: The test dispersion prepared from the fibrous material dispersion had a molecular weight of 1.01 or more, as shown in the following formula (1): α = 1 − ([A] / [B]) (1) (In formula (1), [A] is the height from the bottom of the dispersion to the separation interface, and [B] is the height from the bottom of the dispersion to the top of the dispersion.) The method includes adding a thickener to the fibrous material dispersion so that the degree of sedimentation α obtained according to the following formula is 80% or less, The test dispersion is the fibrous material dispersion itself when the concentration of the fibrous material in the fibrous material dispersion is 0.05% by mass, and when the concentration is not 0.05% by mass, the test dispersion is prepared by concentrating the fibrous material dispersion or diluting it with the same dispersion medium as the dispersion medium so that the concentration is 0.05% by mass.
[14] A resin composition comprising 100 parts by mass of a resin, 0.001 to 50 parts by mass of a fibrous material having an average fiber diameter of 1 to 1,000 nm, and 0.00001 to 5 parts by mass of a thickener.
[15] The resin composition according to claim 14, wherein the resin is a thermoplastic resin.
[16] The tensile elongation at yield (TEy) and the tensile elongation at break (TEb) are related by the following formula: [TEb / TEy]≧1 16. The resin composition according to claim 14 or 15,
[17] The resin composition of any one of Aspects 14 to 16 above, wherein the tensile strength is improved by 1.01 times or more compared to a comparative resin composition having the same composition but not containing the thickener.
[18] A method for producing a resin composition containing a thermoplastic resin and a fibrous material, comprising: Preparing a fibrous material dispersion according to any one of aspects 1 to 12 above; melt-kneading the fibrous material dispersion and the thermoplastic resin; A method comprising:
[19] A method for producing a resin composition containing a thermoplastic resin and a fibrous material, comprising: Preparing a fibrous material dispersion according to any one of aspects 1 to 12 above; drying the fibrous material dispersion to prepare a dry body; Melting and kneading the dried body and the thermoplastic resin; A method comprising: Effect of the Invention
[0013] According to one aspect of the present invention, a fibrous material dispersion can be provided that, even when hydrophobic fibers are used, the generation of agglomerates in piping and / or pumps is extremely low, thereby enabling stabilization of the production process and good dispersion of the fibrous material in the resin, thereby producing a resin composition with good and stable physical properties. [Brief description of the drawings]
[0014] [Figure 1] 13 is an explanatory diagram of a method for calculating the IR index 1730 and the IR index 1030. FIG. [Diagram 2] FIG. 2 is an explanatory diagram of a method for calculating the average substitution degree of hydroxyl groups in cellulose. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Exemplary embodiments of the present invention will be described in detail below, but the present invention is not limited to these embodiments.
[0016] <Fibrous material dispersion> One aspect of the present invention provides a fibrous material dispersion (also simply referred to as a dispersion in the present disclosure) containing a dispersion medium and a fibrous material dispersed in the dispersion medium. In one aspect, the fibrous material is a cellulose fiber. In one aspect, the amount of the fibrous material in the dispersion is 0.01 to 20 parts by mass relative to 100 parts by mass of the dispersion medium.
[0017] In one embodiment, the test dispersion prepared from the fibrous material dispersion has the following formula (1): α = 1 − ([A] / [B]) (1) (In formula (1), [A] is the height from the bottom of the dispersion to the separation interface, and [B] is the height from the bottom of the dispersion to the top of the dispersion.) The sedimentation degree α obtained according to is 80% or less. Here, the test dispersion is the fibrous material dispersion itself when the concentration of the fibrous material in the fibrous material dispersion is 0.05% by mass, and when the concentration is not 0.05% by mass, the test dispersion is prepared by concentrating the fibrous material dispersion or diluting it with the same dispersion medium (i.e., the same substance) as the dispersion medium in the dispersion so that the concentration becomes 0.05% by mass. Dilution is performed by adding a required amount of dispersion medium to the dispersion. Concentration is performed by separating the dispersion into the dispersion medium and the fibrous material using a filter cloth, a membrane filter, centrifugation, etc. 20 ml of the test dispersion is dispensed into a 30 ml glass vial, dispersed with a homogenizer (10,000 rpm for 1 minute), and then 8 ml of the test dispersion is quickly dispensed into a 15 ml screw-top test tube (AS ONE product number: 4-565-06), sealed, and manually shaken to homogenize the dispersion, then left to stand at 23°C and normal pressure for 24 hours. The separation interface is defined using a liquid dispersion stability evaluation device (e.g., "Turbiscan" manufactured by FORMULACTION), and [A] and [B] are measured.
[0018] The sedimentation degree α of the present disclosure is an index of the dispersion stability (difficulty of settling in the dispersion medium) of the fibrous material in the dispersion, and the smaller the value, the less likely the material is to sediment (i.e., the less likely the material is to separate from the fibrous material in the dispersion medium over time or to exude). Since the dispersion of the present disclosure may have various fibrous material concentrations, the sedimentation degree α is measured after adjusting the fibrous material concentration to 0.05 mass%. From the viewpoint of good dispersibility of the fibrous material, the sedimentation degree α is 80% or less, preferably 70% or less, 60% or less, or 50% or less. From the viewpoint of ease of preparation of the dispersion, the sedimentation degree α may be 1% or more, 5% or more, or 10% or more. Methods for controlling the sedimentation degree α of the dispersion of the present disclosure within the above range include controlling the shape of the fibrous material (for example, a method of providing unevenness, fluff, etc. on the surface of the fibrous material), and using various additives (for example, a thickener).
[0019] <Fibrous material> Examples of the fibrous material include cellulose fibers, synthetic polymer fibers, glass fibers, and carbon fibers. In one embodiment, the fibrous material is cellulose fibers, particularly cellulose nanofibers. The cellulose nanofibers refer to cellulose obtained by treating pulp or the like with hot water at 100° C. or higher to hydrolyze and weaken the hemicellulose, and then defibrating the cellulose by a pulverizing method using a high-pressure homogenizer, a microfluidizer, a ball mill, a disk mill, a mixer (e.g., a homomixer), or the like. The cellulose fibers may be chemically modified as described below.
[0020] In one embodiment, the number average fiber diameter of the fibrous material is preferably 1 to 1000 nm from the viewpoint of obtaining a good effect of improving physical properties by the fibrous material. The number average fiber diameter of the fibrous material is more preferably 4 nm or more, more preferably 5 nm or more, more preferably 10 nm or more, more preferably 15 nm or more, even more preferably 20 nm or more, more preferably 500 nm or less, more preferably 450 nm or less, more preferably 400 nm or less, more preferably 350 nm or less, more preferably 300 nm or less, even more preferably 250 nm or less. It is particularly preferable that the fibrous material is a cellulose nanofiber having the above number average fiber diameter.
[0021] The lower limit of the average L / D of the fibrous material (preferably cellulose nanofiber) is preferably 50, more preferably 80, more preferably 100, even more preferably 120, and most preferably 150. The upper limit is not particularly limited, but from the viewpoint of handleability, it is preferably 5000 or less. From the viewpoint of satisfactorily improving the mechanical properties of a resin composition containing a fibrous material with a small amount of fibrous material, it is desirable that the average L / D ratio of the fibrous material is within the above-mentioned range.
[0022] In the present disclosure, the length, diameter, and L / D ratio of each fibrous material are determined by diluting an aqueous dispersion of the fibrous material with a water-soluble solvent (e.g., water, ethanol, tert-butanol, etc.) to 0.01 to 0.1% by mass, dispersing the fibrous material using a high-shear homogenizer (e.g., IKA, product name "Ultra Turrax T18") under processing conditions: rotation speed 25,000 rpm x 5 minutes, casting the homogenized material on mica, and air-drying the material to obtain a measurement sample, which is then measured using a high-resolution scanning electron microscope (SEM) or atomic force microscope (AFM). Specifically, the length (L) and diameter (D) of 100 randomly selected fibrous materials are measured in an observation field where the magnification is adjusted so that at least 100 fibrous materials are observed, and the ratio (L / D) is calculated. The number average value of the length (L), the number average value of the diameter (D), and the number average value of the ratio (L / D) are calculated for the fibrous material.
[0023] The length, diameter, and L / D ratio of the fibrous material in the composition described below can be confirmed by measuring the solid composition as a measurement sample using the above-mentioned measurement method. Alternatively, the length, diameter, and L / D ratio of the fibrous material in the composition can be confirmed by dissolving the resin component in the composition in an organic or inorganic solvent that can dissolve the resin component of the composition, separating the fibrous material, thoroughly washing with the solvent, and then replacing the solvent with pure water to prepare an aqueous dispersion, diluting the fibrous material concentration with pure water to 0.1 to 0.5% by mass, casting on mica, and air-drying the resulting sample using the above-mentioned measurement method. At this time, the measurement is performed on 100 or more randomly selected fibrous materials.
[0024] When the fibrous material is cellulose fiber, the crystallinity of the cellulose fiber is preferably 55% or more. When the crystallinity is within this range, the mechanical properties (strength, dimensional stability) of the cellulose fiber itself are high, so that when the cellulose fiber is dispersed in a resin, the strength and dimensional stability of the resin composition tend to be high. A more preferable lower limit of the crystallinity is 60%, even more preferably 70%, and most preferably 80%. There is no particular upper limit for the crystallinity of the cellulose fiber, and the higher the better, but from the viewpoint of production, a preferable upper limit is 99%.
[0025] Alkali-soluble polysaccharides such as hemicellulose and acid-insoluble components such as lignin are present between the microfibrils and between the microfibril bundles of plant-derived cellulose. Hemicellulose is a polysaccharide composed of sugars such as mannan and xylan, and plays a role in binding the microfibrils together by hydrogen bonding with cellulose. Lignin is a compound having an aromatic ring, and is known to be covalently bonded to hemicellulose in the cell walls of plants. If there is a large amount of impurities such as lignin remaining in the cellulose fibers, discoloration may occur due to heat during processing. Therefore, from the viewpoint of suppressing discoloration of the resin composition during extrusion processing and molding processing, it is desirable to set the crystallinity of the cellulose fibers within the above-mentioned range.
[0026] The degree of crystallinity here, when the cellulose fiber is cellulose type I crystal (derived from natural cellulose), is calculated from the diffraction pattern (2θ / deg. is 10 to 30) obtained by measuring the sample by wide-angle X-ray diffraction, using the Segal method and the following formula. Crystallinity (%) = ([diffraction intensity due to the (200) plane at 2θ / deg. = 22.5] - [diffraction intensity due to amorphous matter at 2θ / deg. = 18]) / [diffraction intensity due to the (200) plane at 2θ / deg. = 22.5] × 100
[0027] When the cellulose fiber is a cellulose II type crystal (derived from regenerated cellulose), the degree of crystallinity can be calculated from the absolute peak intensity h0 at 2θ=12.6° assigned to the (110) plane peak of the cellulose II type crystal in wide-angle X-ray diffraction and the peak intensity h1 from the baseline at this interplanar spacing, according to the following formula: Crystallinity (%) =h1 / h0 ×100
[0028] Known crystalline forms of cellulose include type I, type II, type III, and type IV, of which type I and type II are particularly widely used, and type III and type IV have been obtained on a laboratory scale but are not widely used on an industrial scale. The cellulose fibers (cellulose nanofibers in one embodiment) of the present disclosure are preferably cellulose fibers containing cellulose type I crystals or cellulose type II crystals, since they have relatively high structural mobility and, by dispersing the cellulose fibers in a resin, a resin composition having a lower linear expansion coefficient and superior strength and elongation during tensile and bending deformation can be obtained, and more preferably cellulose fibers containing cellulose type I crystals and having a crystallinity of 55% or more.
[0029] In addition, the degree of polymerization of the cellulose fibers is preferably 100 or more, more preferably 150 or more, more preferably 200 or more, more preferably 300 or more, preferably 400 or more, more preferably 420 or more, more preferably 430 or more, more preferably 440 or more, more preferably 450 or more, and preferably 3500 or less, more preferably 3300 or less, more preferably 3200 or less, more preferably 3100 or less, and more preferably 3000 or less.
[0030] From the viewpoint of processability and mechanical property expression, it is desirable that the polymerization degree of the cellulose fiber is within the above-mentioned range. From the viewpoint of processability, it is preferable that the polymerization degree is not too high, and from the viewpoint of mechanical property expression, it is desirable that the polymerization degree is not too low.
[0031] The degree of polymerization of cellulose fibers means the average degree of polymerization measured according to the reduced specific viscosity method using a copper ethylenediamine solution described in the Verification Test (3) of the "15th Revised Japanese Pharmacopoeia Commentary (published by Hirokawa Shoten)."
[0032] In one embodiment, the weight average molecular weight (Mw) of the cellulose fiber is 100,000 or more, more preferably 200,000 or more. The ratio (Mw / Mn) of the weight average molecular weight to the number average molecular weight (Mn) is 6 or less, preferably 5.4 or less. The larger the weight average molecular weight, the fewer the number of terminal groups of the cellulose molecule. In addition, since the ratio (Mw / Mn) of the weight average molecular weight to the number average molecular weight represents the width of the molecular weight distribution, the smaller the Mw / Mn, the fewer the number of terminals of the cellulose molecule. Since the terminals of the cellulose molecule are the starting points of thermal decomposition, when the cellulose molecule of the cellulose fiber not only has a large weight average molecular weight but also has a narrow molecular weight distribution width, a particularly high heat resistant cellulose fiber and a resin composition containing the cellulose fiber and a resin can be obtained. The weight average molecular weight (Mw) of the cellulose fiber may be, for example, 600,000 or less, or 500,000 or less, from the viewpoint of the availability of the cellulose raw material. From the viewpoint of ease of production of cellulose fibers, the ratio (Mw / Mn) of the weight average molecular weight to the number average molecular weight (Mn) may be, for example, 1.5 or more, or 2 or more. Mw can be controlled within the above range by selecting a cellulose raw material having an Mw appropriate for the purpose, performing a physical treatment and / or a chemical treatment on the cellulose raw material appropriately within a moderate range, and the like. Mw / Mn can also be controlled within the above range by selecting a cellulose raw material having an Mw / Mn appropriate for the purpose, performing a physical treatment and / or a chemical treatment on the cellulose raw material appropriately within a moderate range, and the like. In both the control of Mw and the control of Mw / Mn, examples of the physical treatment include dry or wet grinding using a microfluidizer, ball mill, disk mill, etc., physical treatment that applies mechanical forces such as impact, shear, shear, and friction using a crusher, homomixer, high-pressure homogenizer, ultrasonic device, etc., and examples of the chemical treatment include digestion, bleaching, acid treatment, and regenerated cellulose.
[0033] The weight average molecular weight and number average molecular weight of cellulose referred to here are values determined by dissolving cellulose in N,N-dimethylacetamide containing added lithium chloride and then subjecting the cellulose to gel permeation chromatography using N,N-dimethylacetamide as a solvent.
[0034] Methods for controlling the degree of polymerization (i.e., average degree of polymerization) or molecular weight of cellulose fibers include hydrolysis. The hydrolysis promotes depolymerization of amorphous cellulose inside the cellulose fibers, decreasing the average degree of polymerization. At the same time, the hydrolysis removes impurities such as hemicellulose and lignin in addition to the amorphous cellulose, making the inside of the fibers more porous.
[0035] The hydrolysis method is not particularly limited, and examples thereof include acid hydrolysis, alkali hydrolysis, hydrothermal decomposition, steam explosion, and microwave decomposition. These methods may be used alone or in combination of two or more. In the acid hydrolysis method, for example, α-cellulose obtained as pulp from a fibrous plant is used as a cellulose raw material, and this is dispersed in an aqueous medium, and an appropriate amount of protonic acid, carboxylic acid, Lewis acid, heteropolyacid, etc. is added, and the mixture is heated while stirring, so that the average degree of polymerization can be easily controlled. The reaction conditions such as temperature, pressure, and time at this time vary depending on the cellulose type, cellulose concentration, acid type, acid concentration, etc., but are appropriately adjusted so that the desired average degree of polymerization is achieved. For example, a condition in which cellulose is treated for 10 minutes or more at 100°C or higher under pressure using an aqueous mineral acid solution of 2% by mass or less can be exemplified. Under these conditions, the catalyst component such as acid penetrates into the inside of the cellulose fiber, promoting hydrolysis, reducing the amount of catalyst component used, and making subsequent purification easier. The dispersion of the cellulose raw material during hydrolysis may contain, in addition to water, a small amount of an organic solvent within a range that does not impair the effects of the present invention.
[0036] Alkali-soluble polysaccharides that may be contained in cellulose fibers include hemicellulose, β-cellulose, and γ-cellulose. Alkali-soluble polysaccharides are understood by those skilled in the art as components obtained as the alkali-soluble portion of holocellulose obtained by solvent extraction and chlorine treatment of plants (e.g., wood) (i.e., components obtained by removing α-cellulose from holocellulose). Alkali-soluble polysaccharides are polysaccharides containing hydroxyl groups and have poor heat resistance, and may cause inconveniences such as decomposition when exposed to heat, yellowing during heat aging, and a decrease in the strength of cellulose fibers. Therefore, it is preferable that the content of alkali-soluble polysaccharides in cellulose fibers is low.
[0037] In one embodiment, the average content of alkali-soluble polysaccharides in the cellulose fibers is preferably 20% by mass or less, 18% by mass or less, 15% by mass or less, or 12% by mass or less, based on 100% by mass of the cellulose fibers, from the viewpoint of obtaining good dispersibility of the cellulose fibers. From the viewpoint of ease of production of the cellulose fibers, the content may be 1% by mass or more, 2% by mass or more, or 3% by mass or more.
[0038] The average alkali-soluble polysaccharide content can be determined by the method described in the non-patent literature (Wood Science Experiment Manual, edited by the Japan Wood Research Society, pages 92-97, 2000), by subtracting the α-cellulose content from the holocellulose content (Wise method). This method is understood in the industry as a method for measuring the amount of hemicellulose. The alkali-soluble polysaccharide content is calculated three times for each sample, and the number average of the calculated alkali-soluble polysaccharide contents is taken as the average alkali-soluble polysaccharide content.
[0039] In one embodiment, the average content of acid-insoluble components in the cellulose fibers is preferably 10% by mass or less, 5% by mass or less, or 3% by mass or less, based on 100% by mass of the cellulose fibers, from the viewpoint of avoiding a decrease in heat resistance of the cellulose fibers and the associated discoloration. From the viewpoint of ease of production of the cellulose fibers, the content may be 0.1% by mass or more, 0.2% by mass or more, or 0.3% by mass or more.
[0040] The average acid-insoluble content is determined as a quantitative determination of the acid-insoluble content using the Clason method described in the non-patent literature (Wood Science Experiment Manual, edited by the Japan Wood Research Society, pages 92-97, 2000). This method is understood in the industry as a method for measuring the amount of lignin. The sample is stirred in a sulfuric acid solution to dissolve cellulose, hemicellulose, etc., and then filtered through a glass fiber filter paper, and the resulting residue corresponds to the acid-insoluble content. The acid-insoluble content is calculated from the weight of the acid-insoluble content, and the number average of the acid-insoluble content calculated for the three samples is taken as the average acid-insoluble content.
[0041] The cellulose fibers may be chemically treated (e.g., oxidized or chemically modified using a modifying agent). As an example, fine cellulose fibers obtained by oxidizing cellulose fibers with 2,2,6,6-tetramethylpiperidine-1-oxyl radical as shown in Cellulose (1998) 5, 153-164, followed by washing and mechanical fiberization, may be used.
[0042] The cellulose modification agent can be a compound that reacts with the hydroxyl group of cellulose, and includes an esterification agent, an etherification agent, and a silylating agent. In a preferred embodiment, the chemical modification is acylation using an esterification agent. The esterification agent is preferably an acid halide, an acid anhydride, or a vinyl carboxylate.
[0043] The acid halide may be at least one selected from the group consisting of compounds represented by the following formula (1). R 1 -C(=O)-X (1) (In the formula, R 1 represents an alkyl group having 1 to 24 carbon atoms, an alkenyl group having 2 to 24 carbon atoms, a cycloalkyl group having 3 to 24 carbon atoms, or an aryl group having 6 to 24 carbon atoms, and X is Cl, Br, or I. Specific examples of acid halides include, but are not limited to, acetyl chloride, acetyl bromide, acetyl iodide, propionyl chloride, propionyl bromide, propionyl iodide, butyryl chloride, butyryl bromide, butyryl iodide, benzoyl chloride, benzoyl bromide, and benzoyl iodide. Among them, acid chlorides can be preferably used in terms of reactivity and handling. In addition, in the reaction of acid halides, one or more alkaline compounds may be added to act as a catalyst and neutralize the by-product acidic substances. Specific examples of alkaline compounds include, but are not limited to, tertiary amine compounds such as triethylamine and trimethylamine; and nitrogen-containing aromatic compounds such as pyridine and dimethylaminopyridine.
[0044] As the acid anhydride, any suitable acid anhydride can be used. For example, Saturated aliphatic monocarboxylic acid anhydrides, such as acetic acid, propionic acid, (iso)butyric acid, and valeric acid; unsaturated aliphatic monocarboxylic acid anhydrides, such as (meth)acrylic acid and oleic acid; Alicyclic monocarboxylic acid anhydrides such as cyclohexanecarboxylic acid and tetrahydrobenzoic acid; Aromatic monocarboxylic acid anhydrides such as benzoic acid and 4-methylbenzoic acid; Examples of dibasic carboxylic acid anhydrides include saturated aliphatic dicarboxylic acid anhydrides such as succinic anhydride and adipic acid, unsaturated aliphatic dicarboxylic acid anhydrides such as maleic anhydride and itaconic anhydride, alicyclic dicarboxylic acid anhydrides such as 1-cyclohexene-1,2-dicarboxylic acid anhydride, hexahydrophthalic anhydride and methyltetrahydrophthalic anhydride, and aromatic dicarboxylic acid anhydrides such as phthalic anhydride and naphthalic anhydride; Examples of polybasic carboxylic acid anhydrides having three or more bases include polycarboxylic acids (anhydrides) such as trimellitic anhydride and pyromellitic anhydride. In the reaction of an acid anhydride, one or more of acidic compounds such as sulfuric acid, hydrochloric acid, phosphoric acid, etc., Lewis acids such as metal chlorides, metal triflates, etc., or alkaline compounds such as triethylamine, pyridine, etc. may be added as a catalyst.
[0045] The vinyl carboxylate may be represented by the following formula (1): R-COO-CH=CH2…Formula (1) Preferred is a vinyl carboxylate represented by the formula: {wherein R is any one of an alkyl group having 1 to 24 carbon atoms, an alkenyl group having 2 to 24 carbon atoms, a cycloalkyl group having 3 to 16 carbon atoms, and an aryl group having 6 to 24 carbon atoms.} The vinyl carboxylate is more preferably at least one selected from the group consisting of vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl cyclohexanecarboxylate, vinyl caprylate, vinyl caprate, vinyl laurate, vinyl myristate, vinyl palmitate, vinyl stearate, vinyl pivalate, vinyl octylate, divinyl adipate, vinyl methacrylate, vinyl crotonate, vinyl pivalate, vinyl octylate, vinyl benzoate, and vinyl cinnamate. In the esterification reaction with a vinyl carboxylate, one or more catalysts selected from the group consisting of alkali metal hydroxides, alkaline earth metal hydroxides, alkali metal carbonates, alkaline earth metal carbonates, alkali metal hydrogencarbonates, primary to tertiary amines, quaternary ammonium salts, imidazole and derivatives thereof, pyridine and derivatives thereof, and alkoxides may be added.
[0046] Examples of the alkali metal hydroxides and alkaline earth metal hydroxides include sodium hydroxide, potassium hydroxide, lithium hydroxide, calcium hydroxide, barium hydroxide, etc. Examples of the alkali metal carbonates, alkaline earth metal carbonates, and alkali metal hydrogen carbonates include lithium carbonate, sodium carbonate, potassium carbonate, cesium carbonate, magnesium carbonate, calcium carbonate, barium carbonate, lithium hydrogen carbonate, sodium hydrogen carbonate, potassium hydrogen carbonate, cesium hydrogen carbonate, etc.
[0047] The primary, secondary and tertiary amines refer to primary, secondary and tertiary amines, and specific examples thereof include ethylenediamine, diethylamine, proline, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetramethyl-1,3-propanediamine, N,N,N',N'-tetramethyl-1,6-hexanediamine, tris(3-dimethylaminopropyl)amine, N,N-dimethylcyclohexylamine and triethylamine.
[0048] Examples of imidazole and its derivatives include 1-methylimidazole, 3-aminopropylimidazole, and carbonyldiimidazole.
[0049] Examples of pyridine and its derivatives include N,N-dimethyl-4-aminopyridine and picoline.
[0050] Examples of the alkoxide include sodium methoxide, sodium ethoxide, and potassium t-butoxide.
[0051] Among these esterification reactants, at least one selected from the group consisting of acetic anhydride, propionic anhydride, butyric anhydride, vinyl acetate, vinyl propionate, and vinyl butyrate is particularly preferred from the viewpoint of reaction efficiency, and among these, acetic anhydride and vinyl acetate are preferred.
[0052] The degree of modification of the chemically modified cellulose fiber of this embodiment is expressed as the average degree of substitution of hydroxyl groups (the average number of hydroxyl groups substituted per glucose, which is the basic structural unit of cellulose, also referred to as DS). In one aspect, the DS of the chemically modified cellulose fiber is preferably 0.01 or more and 2.0 or less. If the DS is 0.01 or more, a resin composition containing chemically modified cellulose having a high thermal decomposition onset temperature can be obtained. On the other hand, if the DS is 2.0 or less, an unmodified cellulose skeleton remains in the chemically modified cellulose, so that a resin composition containing chemically modified cellulose having both high tensile strength and dimensional stability derived from cellulose and a high thermal decomposition onset temperature derived from chemical modification can be obtained. The DS is more preferably 0.05 or more, even more preferably 0.1 or more, particularly preferably 0.2 or more, and most preferably 0.3 or more, and more preferably 1.8 or less, even more preferably 1.5 or less, particularly preferably 1.2 or less, and most preferably 1.0 or less.
[0053] When the modifying group of the chemically modified cellulose fiber is an acyl group, the degree of acyl substitution (DS) can be calculated from the reflection infrared absorption spectrum of the esterified cellulose fiber based on the peak intensity ratio between the peak derived from the acyl group and the peak derived from the cellulose skeleton. The peak of the absorption band of C=O based on the acyl group is at 1730 cm -1 The absorption band of CO based on the cellulose backbone appears at 1030 cm -1 The DS of esterified cellulose fibers was calculated by plotting a correlation graph between the DS obtained from solid-state NMR measurements of esterified cellulose fibers (described later) and the modification ratio (IR index 1030), which is defined as the ratio of the peak intensity of the absorption band of C=O based on acyl groups to the peak intensity of the absorption band of CO in the cellulose backbone chain, and then calculating the calibration curve from the correlation graph. Degree of substitution DS = 4.13 × IR index (1030) It can be found by using
[0054] The method for calculating the DS of esterified cellulose fiber by solid-state NMR is as follows: 13C solid-state NMR measurement was performed, and the intensity can be calculated using the area intensity (Inf) of a signal assigned to one carbon atom derived from the modifying group relative to the total area intensity (Inp) of signals assigned to carbons C1-C6 derived from the pyranose ring of cellulose, which appear in the range from 50 ppm to 110 ppm, using the following formula. DS = (Inf) x 6 / (Inp) For example, when the modifying group is an acetyl group, the signal at 23 ppm assigned to -CH3 may be used. Use 13 The conditions for the C solid-state NMR measurement are, for example, as follows: Equipment:Bruker Biospin Avance500WB Frequency: 125.77MHz Measurement method: DD / MAS method Waiting time: 75sec NMR sample tube: 4mmφ Accumulation times: 640 times (approx. 14 hours) MAS: 14,500Hz Chemical shift standard: glycine (external standard: 176.03 ppm)
[0055] The DS heterogeneity ratio (DSs / DSt), defined as the ratio of the degree of modification (DSs) of the fiber surface to the degree of modification (DSt) of the entire fiber of the chemically modified cellulose fiber (which is synonymous with the above-mentioned degree of acyl substitution (DS)), is preferably 1.05 or more. The larger the value of the DS heterogeneity ratio, the more pronounced the heterogeneous structure resembling a sheath-core structure (i.e., a structure in which the fiber surface is highly chemically modified while the fiber center retains a structure close to the original unmodified cellulose structure), and while maintaining high tensile strength and dimensional stability derived from cellulose, it is possible to improve the affinity with the resin when composited with the resin and to improve the dimensional stability of the resin composition. The DS heterogeneity ratio is more preferably 1.1 or more, or 1.2 or more, or 1.3 or more, or 1.5 or more, or 2.0, and from the viewpoint of ease of production of the chemically modified cellulose fiber, it is preferably 30 or less, or 20 or less, or 10 or less, or 6 or less, or 4 or less, or 3 or less. The value of DSs varies depending on the degree of modification of the esterified cellulose, but as an example, it is preferably 0.1 or more, more preferably 0.2 or more, even more preferably 0.3 or more, even more preferably 0.5 or more, and is preferably 3.0 or less, more preferably 2.5 or less, particularly preferably 2.0 or less, even more preferably 1.5 or less, particularly preferably 1.2 or less, and most preferably 1.0 or less. The preferred range of DSt is as described above for the acyl substituent (DS).
[0056] The smaller the coefficient of variation (CV) of the DS heterogeneity of the chemically modified cellulose fiber, the smaller the variation in various physical properties of the resin composition, and therefore the more preferable. The coefficient of variation is preferably 50% or less, or 40% or less, or 30% or less, or 20% or less. The coefficient of variation can be further reduced, for example, by a method in which the cellulose raw material is defibrated and then chemically modified to obtain the chemically modified cellulose fiber (i.e., a sequential method), whereas it can be increased by a method in which the defibration and chemical modification of the cellulose raw material are simultaneously performed (i.e., a simultaneous method). Although the mechanism of this action is not clear, it is considered that in the simultaneous method, chemical modification is more likely to proceed in the thin fibers generated in the early stage of defibration, and when hydrogen bonds between cellulose microfibrils are reduced by chemical modification, defibration proceeds further, resulting in an increase in the coefficient of variation of the DS heterogeneity.
[0057] The coefficient of variation (CV) of the DS heterogeneity ratio is calculated by taking 100 g of an aqueous dispersion of chemically modified cellulose fiber (solid content of 10 mass% or more), freeze-pulverizing 10 g portions of each sample, calculating the DS heterogeneity ratio from the DSt and DSs of the 10 samples, and then using the standard deviation (σ) and arithmetic mean (μ) of the DS heterogeneity ratio among the obtained 10 samples, using the following formula. DS heterogeneity ratio = DSs / DSt Coefficient of variation (%) = standard deviation σ / arithmetic mean μ × 100
[0058] The DSs is calculated as follows. That is, the esterified cellulose powdered by freeze-pulverization is placed on a dish-shaped sample stage with a diameter of 2.5 mm, the surface is pressed down to make it flat, and then measurement is performed by X-ray photoelectron spectroscopy (XPS). The XPS spectrum reflects the constituent elements and chemical bond state of only the surface layer of the sample (typically about a few nm). Peak separation is performed on the obtained C1s spectrum, and DSs can be calculated by the following formula based on the area intensity (Ixf) of the peak assigned to one carbon atom derived from the modifying group relative to the area intensity (Ixp) of the peak (289 eV, CC bond) assigned to carbons C2-C6 derived from the pyranose ring of cellulose. DSs = (Ixf) x 5 / (Ixp) For example, if the modifying group is an acetyl group, after peak separation of the C1s spectrum at 285 eV, 286 eV, 288 eV, and 289 eV, the peak at 289 eV can be used for Ixp and the peak derived from the O-C=O bond of the acetyl group (286 eV) can be used for Ixf. The conditions for the XPS measurement are as follows, for example: Equipment used: ULVAC-Phi VersaProbe II Excitation source: mono.AlKα 15kV×3.33mA Analysis size: Approx. 200 μm φ Photoelectron extraction angle: 45° Capture Area Narrow scan: C 1s, O 1s Pass Energy: 23.5eV
[0059] In one embodiment, the fibrous material is a synthetic polymer fiber, such as polyamide (e.g., polyamide 66) fiber, aramid fiber, Kevlar, polypropylene fiber, polyester fiber, polyurethane fiber, or nanofibers obtained by further defibrating these fibers using the defibration method described below.
[0060] Examples of methods for producing synthetic polymer fibers include melt spinning, wet spinning, electrospinning, carbon dioxide laser supersonic drawing, high-pressure homogenizer defibration, underwater head-on collision, etc. These methods may be used alone or in combination to produce synthetic polymer fibers.
[0061] A combination of two or more types of fibrous materials may be used. The fibrous materials may be surface-treated with a surface modifier, a surfactant, or the like.
[0062] In one embodiment, the fibrous material is hydrophobic. In the present disclosure, hydrophobicity refers to a state in which the hydrophilicity of the molecule is reduced due to a functional group with low polarity or non-polarity. A specific example of a hydrophobic fibrous material is aramid fiber. When the fibrous material is a cellulose fiber (cellulose nanofiber in one embodiment), cellulose itself is a highly hydrophilic material, but the hydroxyl group of cellulose can be esterified by the above-mentioned method such as acetylation, propionylation, butylation, benzylation, or adamantylation to obtain a hydrophobic fibrous material.
[0063] <Dispersion medium> As the dispersion medium of the fibrous material dispersion, liquid media such as water and organic solvents can be used. As the organic solvent, a water-miscible organic solvent that is generally used can be used. As the water-miscible organic solvent, polyols (e.g., polyether polyols such as polypropylene glycol and polyethylene glycol), ethanol, methanol, dimethylformamide, dimethyl sulfoxide, acetonitrile, acetone, acetic acid, t-butanol, etc. can be used. From the viewpoint of handling, water is particularly preferred. In one embodiment, the dispersion medium in the dispersion is water.
[0064] <Thickener> The thickener is not particularly limited as long as it can increase the viscosity of the dispersion medium and stabilize the fibrous material dispersion. The stabilization mentioned here includes improving the phase separation of the fibrous material dispersion (i.e., increasing the affinity between the fibrous material and the dispersion medium), suppressing aggregation of the fibrous material, improving liquid permeability, etc.
[0065] The amount of thickener per 100 parts by mass of the dispersion medium is, from the viewpoint of obtaining a good thickening effect, preferably 0.0001 parts by mass or more, more preferably 0.001 parts by mass or more, and even more preferably 0.005 parts by mass or more, and from the viewpoint of avoiding inconvenience due to the thickener remaining in the resin composition when a resin composition is produced using the dispersion, preferably 2 parts by mass or less, more preferably 1.5 parts by mass or less, and even more preferably 1 part by mass or less.
[0066] Examples of thickeners include polymers having a hydrophilic group (e.g., a hydroxyl group, an amino group, etc.) (e.g., polyacrylamide, polyalkylene oxide, polyacrylic acid and its salts, polysaccharides (e.g., cellulose derivatives, starch, alginic acid and its salts (e.g., sodium alginate), guar gum, gellan gum, gelatin, etc.), polyvinyl alcohol, etc.), and monomers having a hydrophilic group (e.g., propylene glycol, N-vinylacetamide, etc.). These have a good thickening effect in a dispersion medium (a dispersion medium containing water in one embodiment), and contribute to good dispersion of fibrous materials. Among them, one or more selected from the group consisting of polyacrylamide, polyalkylene oxide, polyacrylic acid and its salts, cellulose derivatives, polyvinyl alcohol, and alginic acid and its salts are preferred.
[0067] Examples of the alkylene oxide unit of the polyalkylene oxide include alkylene oxides having 2 to 4 carbon atoms, preferably ethylene oxide and propylene oxide. In a preferred embodiment, the polyalkylene oxide is composed of ethylene oxide units and / or propylene oxide units. A particularly preferred polyalkylene oxide is polyethylene oxide.
[0068] Examples of cellulose derivatives include cellulose ethers (for example, methyl cellulose, carboxymethyl cellulose, carboxyethyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropylmethyl cellulose, etc.).
[0069] The weight average molecular weight of the thickener is preferably 1000 or more, more preferably 5000 or more, and even more preferably 10000 or more, and is preferably 5×10 8 Less than 10, more preferably 8 Less than 5×10, more preferably 7 The following is the result.
[0070] In one embodiment, the thickener is a surfactant. The surfactant has a chemical structure in which a portion having a hydrophilic substituent and a portion having a hydrophobic substituent are covalently bonded. As the surfactant, any of anionic surfactants, nonionic surfactants, amphoteric surfactants, and cationic surfactants can be used, but nonionic surfactants are preferred in that they can better reduce the sedimentation of the fibrous material in the dispersion.
[0071] As the hydrophilic group of the surfactant, from the viewpoint of affinity with fibrous materials (especially cellulose fibers), polyoxyethylene chains, carboxyl groups, and hydroxyl groups are preferred, and polyoxyethylene chains are particularly preferred. Nonionic polyoxyethylene derivatives are particularly preferred. The polyoxyethylene chain length of the polyoxyethylene derivative may be 1 or more, or 4 or more, or 10 or more, or 15 or more. The longer the chain length, the higher the affinity with hydrophobic fibrous materials, but from the viewpoint of the balance with the properties (e.g., mechanical properties, etc.) of the resin composition containing the fibrous material and the resin, the polyoxyethylene chain length may be 60 or less, or 50 or less, or 40 or less, or 30 or less, or 20 or less.
[0072] As the structure of the hydrophobic group of the surfactant, alkyl ether type, alkyl phenyl ether type, rosin ester type, bisphenol A type, β-naphthyl type, styrenated phenyl type, and hardened castor oil type are preferred in terms of high affinity with resin. The number of carbon atoms of the alkyl chain of the hydrophobic group (in the case of alkyl phenyl, the number of carbon atoms excluding the phenyl group) is preferably 5 or more, or 10 or more, or 12 or more, or 16 or more. For example, when the resin is a polyolefin resin, the more carbon atoms of the surfactant, the higher the affinity with the resin. The number of carbon atoms may be, for example, 30 or less, or 25 or less.
[0073] In one embodiment, the dispersion liquid includes a particulate component. The particulate component may be a solid or a liquid. Examples of solids include spherical silica, cellulose nanocrystals, nanoclay, nanotalc, etc., and examples of liquids include the dispersed phase in an emulsion (e.g., polyurethane, polyamide, modified polypropylene, vinyl acetate, ABS, etc.). Examples of the size of the particulate component include 0.001 to 20 μm, or 0.01 to 10 μm, or 0.1 to 1 μm.
[0074] <Dispersion stabilizer> In one embodiment, the dispersion may further include a dispersion stabilizer. The dispersion stabilizer of the present disclosure means a compound that has a function of stably dispersing a fibrous material and improves or controls the dispersion state of the fibrous material in a resin, thereby improving the mechanical properties of a resin composition produced using the dispersion. The dispersion stabilizer is distinguished from the thickener of the present disclosure by its small contribution to the sedimentation degree α of the fibrous material. In one embodiment, the thickener is one whose sedimentation degree (referred to as sedimentation degree B) when added at 2 parts by mass to 100 parts by mass of a dispersion (having a sedimentation degree A) in which a fibrous material is dispersed at a concentration of 0.05% by mass, satisfies the relationship: (sedimentation degree B)<(sedimentation degree A)×0.9, and the dispersion stabilizer is one whose sedimentation degree (referred to as sedimentation degree B) satisfies the relationship: (sedimentation degree A)×0.9≦(sedimentation degree B)≦(sedimentation degree A)×1.1. In a preferred embodiment, the fibrous material is dispersed in the resin composition in the form of a dispersion containing a dispersion stabilizer and a fibrous material dispersed in the dispersion stabilizer. That is, the resin composition is preferably one in which a dispersion in which a fibrous material is dispersed in a dispersion stabilizer is dispersed in a resin. The mass ratio of the fibrous material to the total of the fibrous material and the dispersion stabilizer (100 mass%) is preferably 5 mass% or more, or 10 mass% or more, or 20 mass% or more, and preferably 90 mass% or less, or 80 mass% or less, or 50 mass% or less. The dispersion stabilizer can be at least one selected from the group consisting of surfactants (excluding those included in thickeners), organic compounds with a boiling point of 160°C or more, and resins having a chemical structure capable of highly dispersing the fibrous material, and is preferably at least one selected from the group consisting of surfactants and organic compounds with a boiling point of 160°C or more.
[0075] As the surfactant used as the dispersion stabilizer, any of anionic surfactants, nonionic surfactants, amphoteric surfactants, and cationic surfactants can be used. From the viewpoint of affinity with fibrous materials, however, anionic surfactants and nonionic surfactants are preferred, and nonionic surfactants are more preferred.
[0076] As the hydrophilic group of the surfactant, from the viewpoint of affinity with fibrous materials, polyoxyethylene chain, carboxyl group, and hydroxyl group are preferred, and polyoxyethylene chain is particularly preferred. Nonionic polyoxyethylene derivatives are particularly preferred. The polyoxyethylene chain length of the polyoxyethylene derivative may be 3 or more, or 5 or more, or 10 or more, or 15 or more. The longer the chain length, the higher the affinity with fibrous materials (especially cellulose fibers), but from the viewpoint of balance with the desired properties (e.g., mechanical properties) of the resin composition, the polyoxyethylene chain length may be 60 or less, or 50 or less, or 40 or less, or 30 or less, or 20 or less.
[0077] As the structure of the hydrophobic group of the surfactant, alkyl ether type, alkyl phenyl ether type, rosin ester type, bisphenol A type, β-naphthyl type, styrenated phenyl type, and hardened castor oil type are preferred in terms of high affinity with resin. The number of carbon atoms of the alkyl chain of the hydrophobic group (in the case of alkyl phenyl, the number of carbon atoms excluding the phenyl group) is preferably 5 or more, or 10 or more, or 12 or more, or 16 or more. For example, when the resin is a polyolefin resin, the more carbon atoms of the surfactant, the higher the affinity with the resin. The number of carbon atoms may be, for example, 30 or less, or 25 or less.
[0078] As the hydrophobic group, those having a cyclic structure or those having a bulky and multifunctional structure are more preferred. As the hydrophobic group having a cyclic structure, alkylphenyl ether type, rosin ester type, bisphenol A type, β-naphthyl type, and styrenated phenyl type groups are preferred, and as the one having a multifunctional structure, hydrogenated castor oil type (e.g. hydrogenated castor oil ether) groups are preferred. Rosin ester type and hydrogenated castor oil type are particularly preferred.
[0079] In a preferred embodiment, the surfactant is a polyethylene glycol (PEG)-polypropylene glycol (PPG) copolymer.
[0080] <Aggregation> In a fibrous material dispersion, when aggregates are formed due to entanglement of the fibrous material with each other, the liquid composition becomes non-uniform. The degree of formation of aggregates can be evaluated by taking an appropriate amount of the fibrous material dispersion, sandwiching it between two flat plates (e.g., glass plates), crushing it by sandwiching it with a force of 0.05 MPa, observing the result, and measuring the number and size of the aggregates. For example, the number of aggregates measured by the above method using 0.3 g of the dispersion is preferably 50 or less, or 10 or less, or 1 or less, and the size is preferably 25 mm or less. 2 Less than or equal to 10mm 2 Less than or equal to 1mm 2 The above number and size values are preferably as small as possible.
[0081] <Liquid permeability> When a fibrous material dispersion is passed through a narrow flow path, the liquid permeability may decrease due to the above-mentioned phase separation (i.e., separation and exudation of liquid components) and / or formation of aggregates. A method for evaluating the liquid permeability is to pass the fibrous material dispersion through a strainer with an appropriate mesh size (specifically, 400 μm) and measure the time until clogging occurs. The liquid permeability measured by the above method is preferably 10 minutes or more, 1 hour or more, or 24 hours or more. The higher the liquid permeability of the dispersion, the more preferable it is, but from the viewpoint of ease of production of the dispersion, it may be, for example, 5000 hours or less, 1000 hours or less, or 100 hours or less.
[0082] <Stable supply of fibrous material dispersion> A method for evaluating the stable supply of a fibrous material dispersion includes measuring the supply amount and fibrous material concentration over time when the fibrous material dispersion is transported using a transport device such as a pump, and judging whether the fibrous material dispersion is being supplied stably. In one embodiment, a tube pump with an inner diameter of 5 mm is used, and the fibrous material dispersion is transported to a resin pipe with a diameter of 10 mm under the same transport conditions as the tube pump rotation speed at which distilled water is transported at 150 g / min. The discharged product is received in a container, and its concentration and supply amount (g / min) are measured every minute. When this is done, it is preferable that the standard deviation (n=10) of the supply amount is within 50%, preferably within 10%, more preferably within 5%, and the standard deviation (n=10) of the concentration is within 30%, preferably within 10%, more preferably within 5%.
[0083] One aspect of the present invention is The present invention provides a method for improving the liquid transportability of a fibrous material dispersion liquid that contains a dispersion medium and a fibrous material dispersed in the dispersion medium. The method comprises the steps of: The test dispersion prepared from the fibrous material dispersion had the following formula (1): α = 1 − ([A] / [B]) (1) (In formula (1), [A] is the height from the bottom of the dispersion to the separation interface, and [B] is the height from the bottom of the dispersion to the top of the dispersion.) The method includes adding a thickener to the fibrous material dispersion so that the degree of sedimentation α obtained according to is 80% or less. When the concentration of the fibrous material in the fibrous material dispersion is 0.05% by mass, the test dispersion is the fibrous material dispersion itself, and when the concentration is not 0.05% by mass, the test dispersion is prepared by concentrating the fibrous material dispersion or diluting it with the same dispersion medium as the dispersion medium so that the concentration becomes 0.05% by mass. The method for measuring the degree of sedimentation α, the method for preparing the test dispersion, and the details of the thickener are the same as those described above.
[0084] ≪Resin composition≫ An aspect of the present invention also provides a resin composition comprising a fibrous material and a resin. In one aspect, the fibrous material has an average fiber diameter of 1 to 1000 nm. In one aspect, the resin composition comprises a thickener. In one aspect, the resin composition can be produced using the dispersion of the present disclosure.
[0085] <Resin> The resin may be a thermoplastic resin, a thermosetting resin, or a photocurable resin. The resin may be an elastomer. From the viewpoints of moldability and productivity, a thermoplastic resin is more preferable.
[0086] (thermoplastic resin) When the resin is a thermoplastic resin, the melting point of the thermoplastic resin may be appropriately selected depending on the application of the resin composition, etc. The melting point of the thermoplastic resin can be, for example, 150°C to 190°C or 160°C to 180°C for a resin with a relatively low melting point (e.g., polyolefin resin), and 220°C to 350°C or 230°C to 320°C for a resin with a relatively high melting point (e.g., polyamide resin).
[0087] The thermoplastic resin may preferably be at least one selected from the group consisting of polyolefin-based resins, polyacetate-based resins, polycarbonate-based resins, polyamide-based resins, polyester-based resins, polyphenylene ether-based resins, and acrylic-based resins.
[0088] The polyolefin resin preferred as the thermoplastic resin is a polymer obtained by polymerizing olefins (e.g., α-olefins) and / or alkenes as monomer units.Specific examples of the polyolefin resin include ethylene (co)polymers such as low-density polyethylene (e.g., linear low-density polyethylene), high-density polyethylene, ultra-low-density polyethylene, and ultra-high-molecular-weight polyethylene, polypropylene (co)polymers such as polypropylene, ethylene-propylene copolymer, and ethylene-propylene-diene copolymer, and copolymers of ethylene and α-olefins such as ethylene-acrylic acid copolymer, ethylene-methyl methacrylate copolymer, and ethylene-glycidyl methacrylate copolymer.
[0089] Here, the most preferred polyolefin resin is polypropylene. In particular, polypropylene having a melt mass flow rate (MFR) of 3 g / 10 min or more and 30 g / 10 min or less, measured at 230 ° C. and a load of 21.2 N according to ISO1133, is preferred. The lower limit of MFR is more preferably 5 g / 10 min, even more preferably 6 g / 10 min, and most preferably 8 g / 10 min. The upper limit is more preferably 25 g / 10 min, even more preferably 20 g / 10 min, and most preferably 18 g / 10 min. From the viewpoint of improving the toughness of the resin composition, it is desirable that MFR does not exceed the above upper limit, and from the viewpoint of the flowability of the resin composition, it is desirable that MFR does not exceed the above lower limit.
[0090] In addition, in order to increase the affinity with fibrous materials (especially cellulose fibers), acid-modified polyolefin resins can also be suitably used. As the acid used for acid modification, mono- or polycarboxylic acids can be used, and examples thereof include maleic acid, fumaric acid, succinic acid, phthalic acid and their anhydrides, and citric acid. Maleic acid or its anhydride is particularly preferred because it is easy to increase the modification rate. There is no particular restriction on the modification method, but a method in which a polyolefin resin is heated to a melting point or higher in the presence or absence of a peroxide and melt-kneaded is common. As the polyolefin resin to be acid-modified, all of the above-mentioned polyolefin resins can be used, but polypropylene is particularly suitable. The acid-modified polypropylene resin may be used alone, but it is more preferable to use it in combination with an unmodified polypropylene resin in order to adjust the modification rate of the resin as a whole. In this case, the ratio of the acid-modified polypropylene resin to all polypropylene resins is preferably 0.5% by mass to 50% by mass. A more preferred lower limit is 1 mass%, or 2 mass%, or 3 mass%, or 4 mass%, or 5 mass%. A more preferred upper limit is 45 mass%, or 40 mass%, or 35 mass%, or 30 mass%, or 20 mass%. In order to maintain the interfacial strength between the resin and the fibrous material (particularly cellulose fiber), a content equal to or higher than the lower limit is preferred, and in order to maintain the ductility of the resin, a content equal to or lower than the upper limit is preferred.
[0091] The melt mass flow rate (MFR) of the acid-modified polypropylene resin measured in accordance with ISO1133 at 230°C under a load of 21.2 N is preferably 50 g / 10 min or more, 100 g / 10 min or more, 150 g / 10 min or more, or 200 g / 10 min or more from the viewpoint of enhancing the affinity at the interface between the resin and the fibrous material (particularly cellulose fiber). The upper limit is not particularly limited, but is preferably 500 g / 10 min from the viewpoint of maintaining mechanical strength.
[0092] Examples of polyamide-based resins that are preferable as the thermoplastic resin include polyamides obtained by polycondensation reaction of lactams (e.g., polyamide 6, polyamide 11, polyamide 12, etc.); diamines (e.g., 1,6-hexanediamine, 2-methyl-1,5-pentanediamine, 1,7-heptanediamine, 2-methyl-1-6-hexanediamine, 1,8-octanediamine, 2-methyl-1,7-heptanediamine, 1,9-nonanediamine, 2-methyl-1,8-octanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine, m-xylylenediamine, etc.) and dicarboxylic acids (e.g., butanedioic acid, pentanedioic acid, hexanedioic acid, , heptanedioic acid, octanedioic acid, nonanedioic acid, decanedioic acid, benzene-1,2-dicarboxylic acid, benzene-1,3-dicarboxylic acid, benzene-1,4-dicarboxylic acid, cyclohexane-1,3-dicarboxylic acid, cyclohexane-1,4-dicarboxylic acid, etc.) (for example, polyamide 6,6, polyamide 6,10, polyamide 6,11, polyamide 6,12, polyamide 6,T, polyamide 6,I, polyamide 9,T, polyamide 10,T, polyamide 2M5,T, polyamide MXD,6, polyamide 6,C, polyamide 2M5,C, etc.); and copolymers in which these are copolymerized (for example, polyamide 6,T / 6,I, etc.).
[0093] Among these polyamide resins, aliphatic polyamides such as polyamide 6, polyamide 11, polyamide 12, polyamide 6,6, polyamide 6,10, polyamide 6,11, and polyamide 6,12, and alicyclic polyamides such as polyamide 6,C and polyamide 2M5,C are more preferred.
[0094] From the viewpoint of improving the heat resistance of the resin composition, the melting point of the polyamide resin is preferably 220°C or more, or 230°C or more, or 240°C or more, or 245°C or more, or 250°C or more, and from the viewpoint of ease of production of the resin composition, the melting point is preferably 350°C or less, or 320°C or less, or 300°C or less.
[0095] The terminal carboxyl group concentration of the polyamide resin is not particularly limited, but is preferably 20 μmol / g or more, or 30 μmol / g or more, and preferably 150 μmol / g or less, or 100 μmol / g or less, or 80 μmol / g or less.
[0096] In the polyamide resin, the ratio of carboxyl end groups to all end groups ([COOH] / [total end groups]) is preferably 0.30 or more, or 0.35 or more, or 0.40 or more, or 0.45 or more from the viewpoint of dispersibility of fibrous materials (particularly cellulose fibers) in the resin composition, and is preferably 0.95 or less, or 0.90 or less, or 0.85 or less, or 0.80 or less from the viewpoint of the color tone of the resin composition.
[0097] The terminal group concentration of the polyamide resin can be adjusted by a known method, such as adding a terminal regulator (e.g., a diamine compound, a monoamine compound, a dicarboxylic acid compound, a monocarboxylic acid compound, an acid anhydride, a monoisocyanate, a monoacid halide, a monoester, a monoalcohol, etc.) that reacts with the terminal group during polymerization of the polyamide to the polymerization liquid so as to obtain a predetermined terminal group concentration.
[0098] Examples of the terminal regulator that reacts with the terminal amino group include aliphatic monocarboxylic acids such as acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecanoic acid, myristic acid, palmitic acid, stearic acid, pivalic acid, and isobutyric acid; alicyclic monocarboxylic acids such as cyclohexanecarboxylic acid; aromatic monocarboxylic acids such as benzoic acid, toluic acid, α-naphthalenecarboxylic acid, β-naphthalenecarboxylic acid, methylnaphthalenecarboxylic acid, and phenylacetic acid; and mixtures of a plurality of terminal regulators selected from the above. Among these, from the viewpoints of reactivity, stability of the blocked terminal, and cost, one or more terminal regulators selected from the group consisting of acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecanoic acid, myristic acid, palmitic acid, stearic acid, and benzoic acid are preferred, and acetic acid is most preferred.
[0099] Examples of the terminal regulator that reacts with the terminal carboxyl group include aliphatic monoamines such as methylamine, ethylamine, propylamine, butylamine, hexylamine, octylamine, decylamine, stearylamine, dimethylamine, diethylamine, dipropylamine, dibutylamine, etc., alicyclic monoamines such as cyclohexylamine, dicyclohexylamine, etc., aromatic monoamines such as aniline, toluidine, diphenylamine, naphthylamine, etc., and any mixtures thereof. Among these, one or more terminal regulators selected from the group consisting of butylamine, hexylamine, octylamine, decylamine, stearylamine, cyclohexylamine, and aniline are preferred in terms of reactivity, boiling point, stability of the blocked terminal, price, etc.
[0100] The concentration of amino end groups and carboxyl end groups of the polyamide resin is 1 It can be determined from the integral value of the characteristic signal corresponding to each terminal group by H-NMR. This method is preferable in terms of accuracy and simplicity. More specifically, it is recommended to use the method described in JP-A-7-228775, use deuterated trifluoroacetic acid as the measurement solvent, and set the number of integration scans to 300 or more.
[0101] The intrinsic viscosity [η] of the polyamide resin measured under the condition of 30°C in concentrated sulfuric acid is preferably 0.6 to 2.0 dL / g, or 0.7 to 1.4 dL / g, or 0.7 to 1.2 dL / g, or 0.7 to 1.0 dL / g, from the viewpoint that the fluidity in the mold is good and the appearance of the molded piece is good when the resin composition is injection molded. In the present disclosure, the "intrinsic viscosity" is synonymous with the viscosity generally called the limiting viscosity. The intrinsic viscosity is obtained by measuring the ηsp / c of several measurement solvents having different concentrations under the temperature condition of 30°C in 96% concentrated sulfuric acid, deriving the relational equation between each of the ηsp / c and the concentration (c), and extrapolating the concentration to zero. The value extrapolated to zero is the intrinsic viscosity. Details of the above method are described, for example, in Polymer Process Engineering (Prentice-Hall, Inc. 1994), pages 291 to 294, etc. From the viewpoint of accuracy, it is desirable to set the concentrations in the measurement solvents having different concentrations to at least four points (for example, 0.05 g / dL, 0.1 g / dL, 0.2 g / dL, and 0.4 g / dL).
[0102] As the polyester resin preferred as the thermoplastic resin, one or more selected from polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), polybutylene adipate terephthalate (PBAT), polyhydroxyalkanoic acid (PHA), polylactic acid (PLA), polyarylate (PAR), etc. can be used. Among them, PET, PBS, PBSA, PBT and PEN are more preferred, and PBS, PBSA and PBT are particularly preferred.
[0103] The terminal groups of the polyester resin can be arbitrarily changed by the monomer ratio during polymerization, the presence or absence and amount of addition of a terminal stabilizer, etc. The ratio of carboxyl terminal groups to all terminal groups of the polyester resin ([COOH] / [total terminal groups]) is preferably 0.30 or more, or 0.35 or more, or 0.40, or 0.45 from the viewpoint of dispersibility of fibrous materials (particularly cellulose fibers) in the resin composition, and is preferably 0.95 or less, or 0.90 or less, or 0.85 or less, or 0.80 or less from the viewpoint of the color tone of the resin composition.
[0104] As the polyacetal resin preferred as the thermoplastic resin, homopolyacetal made from formaldehyde and copolyacetal containing trioxane as the main monomer and 1,3-dioxolane as the comonomer component are generally used, and although both can be used, copolyacetal is preferred from the viewpoint of thermal stability during processing. The amount of the structure derived from the comonomer component (e.g., 1,3-dioxolane) is preferably 0.01 mol% or more, or 0.05 mol% or more, or 0.1 mol% or more, or 0.2 mol% or more from the viewpoint of thermal stability during extrusion processing and molding processing, and is preferably 4 mol% or less, or 3.5 mol% or less, or 3.0 mol% or less, or 2.5 mol% or less, or 2.3 mol% or less from the viewpoint of mechanical strength.
[0105] (thermosetting resin) Examples of thermosetting resins include bisphenol type epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol S type epoxy resin, bisphenol E type epoxy resin, bisphenol M type epoxy resin, bisphenol P type epoxy resin, and bisphenol Z type epoxy resin; novolac type epoxy resins such as bisphenol A novolac type epoxy resin, phenol novolac type epoxy resin, and cresol novolac epoxy resin; biphenyl type epoxy resin, biphenyl aralkyl type epoxy resin, aryl alkylene type epoxy resin, tetraphenylol ethane type epoxy resin, naphthalene type epoxy resin, anthracene type epoxy resin, phenoxy type epoxy resin, dicyclopentadiene type epoxy resin, norbornene type epoxy resin, adamantane type epoxy resin, fluorene type epoxy resin, glycidyl methacrylate copolymer epoxy resin, cyclohexylmaleimide and glycidyl methacrylate copolymer epoxy resin, epoxy modified polybutadiene rubber derivative, CTBN modified epoxy resin, trimethylolpropane polyglycidyl ether, Phenyl-1,3-diglycidyl ether, biphenyl-4,4'-diglycidyl ether, 1,6-hexanediol diglycidyl ether, diglycidyl ether of ethylene glycol or propylene glycol, sorbitol polyglycidyl ether, tris(2,3-epoxypropyl)isocyanurate, triglycidyl tris(2-hydroxyethyl)isocyanurate, novolac-type phenolic resins such as phenol novolac resin, cresol novolac resin, and bisphenol A novolac resin, unmodified resol phenolic resin, paulownia wood Examples of the resin include phenolic resins such as resol-type phenolic resins, such as oil-modified resol phenolic resins modified with oil, linseed oil, walnut oil, etc.; triazine ring-containing resins, such as phenoxy resins, urea (urea) resins, and melamine resins; unsaturated polyester resins, bismaleimide resins, diallyl phthalate resins, silicone resins, resins having a benzoxazine ring, norbornene resins, cyanate resins, isocyanate resins, urethane resins, benzocyclobutene resins, maleimide resins, bismaleimide triazine resins, polyazomethine resins, and thermosetting polyimides.
[0106] (light curing resin) Examples of photocurable resins include (meth)acrylate resins, vinyl resins, and epoxy resins. These are generally classified into radical reaction types in which a monomer reacts with radicals generated by light, and cationic reaction types in which a monomer undergoes cationic polymerization, according to the reaction mechanism. Examples of radical reaction type monomers include (meth)acrylate compounds and vinyl compounds (e.g., certain vinyl ethers). Examples of cationic reaction types include epoxy compounds and certain vinyl ethers. For example, an epoxy compound that can be used as a cationic reaction type can be a monomer for both thermosetting resins and photocurable resins.
[0107] The (meth)acrylate compound is a compound having one or more (meth)acrylate groups in the molecule. Examples of the (meth)acrylate compound include monofunctional (meth)acrylates, polyfunctional (meth)acrylates, epoxy acrylates, polyester acrylates, and urethane acrylates.
[0108] Examples of vinyl compounds include vinyl ether, styrene, and styrene derivatives. Examples of vinyl ether include ethyl vinyl ether, propyl vinyl ether, hydroxyethyl vinyl ether, and ethylene glycol divinyl ether. Examples of styrene derivatives include methyl styrene and ethyl styrene. Other examples of vinyl compounds include triallyl isocyanurate and trimethallyl isocyanurate.
[0109] As a raw material for the photocurable resin, a so-called reactive oligomer may be used. Examples of the reactive oligomer include an oligomer having any combination selected from a (meth)acrylate group, an epoxy group, a urethane bond, and an ester bond in the same molecule, such as a urethane acrylate having a (meth)acrylate group and a urethane bond in the same molecule, a polyester acrylate having a (meth)acrylate group and an ester bond in the same molecule, and an epoxy acrylate derived from an epoxy resin having an epoxy group and a (meth)acrylate group in the same molecule.
[0110] (Elastomer) Examples of elastomers (i.e. rubber) include natural rubber (NR), butadiene rubber (BR), styrene-butadiene copolymer rubber (SBR), isoprene rubber (IR), butyl rubber (IIR), acrylonitrile-butadiene rubber (NBR), acrylonitrile-styrene-butadiene copolymer rubber, chloroprene rubber, styrene-isoprene copolymer rubber, styrene-isoprene-butadiene copolymer rubber, isoprene-butadiene copolymer rubber, chlorosulfonated polyethylene rubber, modified natural rubber (epoxidized natural rubber (ENR), hydrogenated natural rubber, deproteinized natural rubber, etc.), ethylene-propylene copolymer rubber, acrylic rubber, epichlorohydrin rubber, polysulfide rubber, silicone rubber, fluororubber, urethane rubber, and the like.
[0111] The amount of the fibrous material relative to 100 parts by mass of the resin (in one embodiment, the thermoplastic resin) is preferably within the range of 0.001 to 100 parts by mass. The lower limit of the amount of the fibrous material is more preferably 0.01 parts by mass, even more preferably 0.1 parts by mass, and most preferably 1 part by mass. The upper limit of the amount of the fibrous material is more preferably 80 parts by mass, even more preferably 70 parts by mass, and most preferably 50 parts by mass. From the viewpoint of the balance between processability and mechanical properties, it is desirable to set the amount of the fibrous material within the above-mentioned range.
[0112] In one embodiment, the amount of thickener per 100 parts by weight of resin (in one embodiment, thermoplastic resin) may preferably be 0.00001 parts by weight or more, or 0.0001 parts by weight or more, or 0.001 parts by weight or more, or 0.01 parts by weight or more, and may preferably be 5 parts by weight or less, or 3% by weight or less, or 1% by weight or less, or 0.5% by weight or less.
[0113] The ratio of the tensile elongation at yield TEy to the tensile elongation at break TEb (TEb / TEy) of the resin composition of the present disclosure is preferably large from the viewpoint of improving elongation due to improved dispersibility of the fibrous material, and is preferably 1.0 or more, or 1.5 or more, or 2.0 or more. When the above ratio is large, the resin composition yields before breaking and exhibits good elongation. The above ratio is preferably large from the viewpoint of improving elongation, but in one embodiment, from the viewpoint of ease of production, it may be 1000 or less, 100 or less, or 10 or less.
[0114] When the resin composition of the present disclosure contains a thickener, the ratio of the tensile strength of the resin composition to the tensile strength of a comparative resin composition having the same composition but without the thickener is preferably larger from the viewpoint of improving the strength due to the improved dispersibility of the fibrous material, and is preferably 1.01 times or more, or 1.05 times or more, or 1.10 times or more, or 1.15 times or more. The higher the ratio, the more preferable it is from the viewpoint of improving elongation, but from the viewpoint of ease of production, in one embodiment, it may be 100 times or less, 10 times or less, or 5 times or less.
[0115] <Method for producing resin composition> When the resin is a thermoplastic resin, the fibrous material dispersion of the present disclosure or a dried product obtained by drying the dispersion (hereinafter, simply referred to as a dried product) can be kneaded with a thermoplastic resin to produce a resin composition. - a method in which a resin monomer is mixed with a dispersion or a dried product of a fibrous material, a polymerization reaction is carried out, the resulting resin composition is extruded into a strand shape, and cooled and solidified in a water bath to obtain a pellet-shaped molded product; - A method in which a mixture of a resin and a dispersion or a dried fibrous material is melt-kneaded using a single-screw or twin-screw extruder, extruded into a strand shape, and cooled and solidified in a water bath to obtain a pellet-shaped molded product; - A method in which a mixture of a resin and a dispersion or a dried material of a fibrous material is melt-kneaded using a single-screw or twin-screw extruder, extruded into a rod or tube, and cooled to obtain an extrusion molded product; - A method in which a mixture of a resin and a dispersion or a dried fibrous material is melt-kneaded using a single-screw or twin-screw extruder, and extruded through a T-die to obtain a sheet or film-like molded product; In a preferred embodiment, a mixture of the resin and the fibrous material dispersion or dried material is melt-kneaded using a single-screw or twin-screw extruder, extruded into a strand shape, and cooled and solidified in a water bath to obtain a pellet-shaped molded product. A specific example of a method for melt-kneading a resin and a fibrous material dispersion or a dried material includes a method in which a resin and a fibrous material dispersion or a dried material that have been transported are mixed in a desired ratio and then melt-kneaded. When the resin is a thermoplastic resin, the minimum processing temperatures recommended by thermoplastic resin suppliers are 255 to 270°C for nylon 66, 225 to 240°C for nylon 6, 170 to 190°C for polyacetal resin, and 160 to 180°C for polypropylene. The heating temperature setting is preferably in the range of 20°C higher than these recommended minimum processing temperatures. By setting the mixing temperature within this temperature range, the fibrous material and the resin can be mixed uniformly.
[0116] Resin compositions containing a thermoplastic resin as a resin can be provided in various shapes. Specifically, resin pellets, sheets, fibers, plates, rods, etc. can be mentioned, but the resin pellet shape is more preferred from the viewpoint of ease of post-processing and ease of transportation. Preferred pellet shapes in this case include round, elliptical, and cylindrical shapes, which vary depending on the cutting method used during extrusion processing. Pellets cut by a cutting method called underwater cutting are often round, pellets cut by a cutting method called hot cutting are often round or elliptical, and pellets cut by a cutting method called strand cutting are often cylindrical. In the case of round pellets, the preferred size is a pellet diameter of 1 mm or more and 3 mm or less. In the case of cylindrical pellets, the preferred diameter is 1 mm or more and 3 mm or less, and the preferred length is 2 mm or more and 10 mm or less. It is desirable to set the above diameter and length to the lower limit or more from the viewpoint of operational stability during extrusion, and it is desirable to set them to the upper limit or less from the viewpoint of bite into the molding machine during post-processing.
[0117] The resin composition containing a thermoplastic resin as a resin can be used as various resin molded products. There is no particular limitation on the manufacturing method of the resin molded product, and any manufacturing method may be used, but injection molding, extrusion molding, blow molding, inflation molding, foam molding, etc. can be used. Among these, injection molding is most preferable from the viewpoint of design and cost.
[0118] When the resin is a thermosetting resin or a photocurable resin, the resin composition can be produced by, for example, a method of thoroughly dispersing a fibrous material dispersion or a dried body in a resin solution or a resin powder dispersion and drying it, a method of thoroughly dispersing a fibrous material dispersion or a dried body in a resin monomer liquid and polymerizing it by heat, UV irradiation, a polymerization initiator, etc., a method of thoroughly impregnating a molded body (e.g., a sheet, a powder particle molded body, etc.) made of a dried body of a fibrous material dispersion with a resin solution or a resin powder dispersion and drying it, a method of thoroughly impregnating a molded body made of a dried body of a fibrous material dispersion with a resin monomer liquid and polymerizing it by heat, UV irradiation, a polymerization initiator, etc. When curing, various polymerization initiators, curing agents, curing accelerators, polymerization inhibitors, etc. can be blended.
[0119] When the resin is a thermosetting resin or a photocurable resin, a method may be used in which an uncured or semi-cured sheet called a prepreg is prepared, the prepreg is made into a single layer or a laminate, and the resin is cured and molded by applying pressure and heat. Examples of the method of applying pressure and heat include a press molding method, an autoclave molding method, a bagging molding method, a wrapping tape method, and an internal pressure molding method.
[0120] When the resin is a photocurable resin, various curing methods using active energy rays can be used to produce a resin molded product.
[0121] When the resin is an elastomer, the resin composition can be produced by a method of kneading the dried fibrous material dispersion with the raw rubber in a dry state, or a method of dispersing or dissolving the fibrous material dispersion or the dried fibrous material dispersion with the raw rubber in a dispersion medium, and then drying and mixing. As a mixing method, a mixing method using a homogenizer is preferred in that it can apply high shear force and pressure to promote dispersion, but other methods such as a propeller type stirring device, a rotary stirring device, an electromagnetic stirring device, and manual stirring can also be used. The resin composition containing the elastomer is molded using a desired molding method such as mold molding, injection molding, extrusion molding, hollow molding, and foam molding to obtain an unvulcanized molded body of a desired shape such as a sheet, pellet, or powder. The unvulcanized molded body can be vulcanized by heat treatment or the like as necessary to obtain a resin molded body.
[0122] The resin molded product containing a thermoplastic resin or an elastomer may be partially (e.g., several portions) melted by heat treatment and then bonded to, for example, a resin or metal substrate. The resin molded product may be a coating applied to a resin or metal substrate, or may form a laminate with the substrate. The sheet-, film-, or fiber-shaped resin molded product may be subjected to secondary processing such as annealing, etching, corona treatment, plasma treatment, grain transfer, cutting, and surface polishing.
[0123] The resin composition of the present disclosure has improved transportability of the fibrous material, allowing for stable production and exhibiting stable physical properties with little variation. EXAMPLES
[0124] The present invention will be further described with reference to examples, but the present invention is not limited to these examples.
[0125] [Ingredients and evaluation method] The raw materials used and the evaluation methods are described below.
[0126] <Thermoplastic resin (polyamide resin)> "UBE Nylon 1013B" manufactured by Ube Industries, Ltd. Polyamide 6 (hereinafter referred to as PA) Carboxyl end group ratio: ([COOH] / [total end groups]) = 0.59
[0127] <Thermoplastic resin (polypropylene resin)> Prime Polypro J105G Made by Prime Polymer
[0128] <Fibrous material (cellulose fiber)> Cellulose fiber A (hereinafter sometimes abbreviated as CNF-A) After cutting the filter paper, 1 part by mass was stirred in 30 parts by mass of dimethyl sulfoxide (DMSO) at room temperature for 1 hour at 500 rpm using a single-shaft stirrer (DKV-1 φ125 mm dissolver manufactured by IMEX Co., Ltd.) at room temperature for 1 hour. Then, the mixture was fed to a bead mill (NVM-1.5 manufactured by IMEX Co., Ltd.) using a hose pump and circulated for 180 minutes using only DMSO to obtain 31 parts by mass of fine cellulose fiber slurry (S1, DMSO solvent) with a solid content of 3.2% by mass. During circulation operation, the rotation speed of the bead mill was 2500 rpm, the peripheral speed was 12 m / s, the beads used were made of zirconia, had a diameter of 2.0 mm, and a filling rate of 70% (the slit gap of the bead mill was 0.6 mm). During circulation operation, the slurry temperature was controlled at 40°C using a chiller to absorb heat generated by friction. 30 parts by mass of pure water was added to the slurry S1, and the mixture was thoroughly stirred, then concentrated in a dehydrator. The obtained wet cake was dispersed again in 30 parts by mass of pure water, stirred, and concentrated. This washing procedure was repeated a total of five times to remove DMSO, and 10 parts by mass of a fine cellulose fiber cake (K1, water solvent) with a solid content of 10% by mass was obtained.
[0129] (Acetylation step) The obtained cellulose fiber precursor A was acetylated to obtain cellulose fiber A. After the slurry S2 in Example 2 was put into an explosion-proof disperser tank, 3.2 parts by mass of vinyl acetate and 0.49 parts by mass of sodium bicarbonate were added, the temperature inside the tank was set to 50°C, and stirring was performed for 120 minutes to obtain 35 parts by mass of a slurry (DMSO solvent) with a solid content of 2.9% by mass. To stop the reaction, 30 parts by mass of pure water was added and thoroughly stirred, and then the mixture was concentrated in a dehydrator. The obtained wet cake was dispersed again in 30 parts by mass of pure water, stirred, and concentrated. The washing operation was repeated a total of five times to remove unreacted reagents and solvents, and 10 parts by mass of an acetylated fine cellulose fiber cake (K3, water solvent) with a solid content of 10% by mass was obtained. Average fiber diameter = 90 nm Crystallinity = 80% Degree of denaturation (DS) = 1.02 Mw=360000, Mw / Mn=2 Average alkali-soluble polysaccharide content: 8.3% by mass
[0130] Cellulose fiber B (hereinafter sometimes abbreviated as CNF-B) A slurry of CNF-B was obtained in the same manner as in the production of CNF-A, except that the temperature in the tank was 40°C and the stirring time was 60 minutes. The properties of the obtained CNF were evaluated by the method described below. The results are shown below. Average fiber diameter = 90 nm Crystallinity = 82% Degree of denaturation (DS) = 0.50 Mw=410000, Mw / Mn=3.2 Average alkali-soluble polysaccharide content: 7.1% by mass
[0131] Cellulose fiber C (hereinafter sometimes abbreviated as CNF-C) A slurry of CNF-B was obtained in the same manner as in the production of CNF-A, except that the temperature in the tank was 30°C and the stirring time was 30 minutes. The properties of the obtained CNF were evaluated by the method described below. The results are shown below. Average fiber diameter = 92 nm Crystallinity = 84% Degree of denaturation (DS) = 0.30 Mw=380000, Mw / Mn=2.5 Average alkali-soluble polysaccharide content: 7.5% by mass
[0132] <Evaluation of cellulose fibers> The physical properties of the cellulose fibers were evaluated using a porous sheet prepared by the following method. [Porous sheet] First, the wet cake was added to tert-butanol, and further dispersed in a mixer or the like until no aggregates were formed. The concentration was adjusted to 0.5% by mass per 0.5 g of cellulose fiber solids. 100 g of the resulting tert-butanol dispersion was filtered on filter paper, dried at 150°C, and the filter paper was peeled off to obtain a sheet. The air resistance of this sheet was 10 g / m2. 2 The porous sheets with a permeability of 100 sec / 100 ml or less were used as measurement samples. The basis weight W (g / m2) of the sample left standing for one day in an environment of 23°C and 50% RH 2 After measuring the air permeability, the air permeability resistance R (sec / 100ml) was measured using an Oken air permeability tester (manufactured by Asahi Seiko Co., Ltd., model EG01). 2 The value per unit area was calculated. Weight 10g / m 2 Air resistance per unit (sec / 100ml) = R / W x 10
[0133] [DS] The infrared spectrum of the porous sheet at five points was measured by the ATR-IR method using a Fourier transform infrared spectrophotometer (FT / IR-6200 manufactured by JASCO Co., Ltd.) The infrared spectrum measurement was performed under the following conditions. Accumulation count: 64 times, Wavenumber resolution: 4cm -1 , Measurement wave number range: 4000~600cm -1 , ATR crystal: Diamond, Incident angle: 45° From the obtained IR spectrum, the IR index was calculated according to the following formula (1): IR index = H1730 / H1030 (1) In the formula, H1730 and H1030 are at 1730 cm -1 , 1030cm -1 (absorption band of CO stretching vibration of cellulose backbone chain) -1 and 1500cm -1 The line connecting the -1 and 1500cm -1 The line connecting these points is taken as the baseline, and the absorbance is calculated when this baseline is taken as 0. Then, the average degree of substitution at each measurement site was calculated from the IR index according to the following formula (2), and the average value was taken as DS. DS = 4.13 × IR index (2)
[0134] [Crystallization degree] The porous sheet was subjected to X-ray diffraction measurement, and the crystallinity was calculated according to the following formula. Crystallinity (%)=[I (200) -I (amorphous) ] / I (200) ×100 I (200) : Diffraction peak intensity due to 200 plane (2θ=22.5°) in cellulose I crystal I (amorphous) : The halo peak intensity due to the amorphous phase in cellulose I crystals, which is the peak intensity at an angle 4.5° lower than the diffraction angle of the 200 plane (2θ=18.0°)
[0135] (X-ray diffraction measurement conditions) Equipment: MiniFlex (Rigaku Corporation) Operation axis 2θ / θ Source CuKα Measurement method: Continuous Voltage 40kV Current 15mA Starting angle 2θ=5° End angle 2θ=30° Sampling width 0.020° Scan speed: 2.0° / min Sample: A porous sheet is attached onto the sample holder.
[0136] [Average fiber diameter] The wet cake was diluted to 0.01% by mass with tert-butanol, dispersed using a high-shear homogenizer (IKA, product name "Ultra Turrax T18") at 25,000 rpm for 5 minutes, cast onto mica, air-dried, and measured with a high-resolution scanning microscope. The magnification was adjusted so that at least 100 cellulose fibers were observed, and the long diameter (L) of 100 randomly selected cellulose fibers was measured, and the arithmetic average of the 100 cellulose fibers was calculated.
[0137] [Weight average molecular weight (Mw), number average molecular weight (Mn) and Mw / Mn ratio] 0.88 g of the porous sheet was weighed, cut into small pieces with scissors, lightly stirred, 20 mL of pure water was added, and left for one day. Next, the water and solids were separated by centrifugation. Next, 20 mL of acetone was added, lightly stirred, and left for one day. Next, the acetone and solids were separated by centrifugation. Next, 20 mL of N,N-dimethylacetamide was added, lightly stirred, and left for one day. N,N-dimethylacetamide and solids were separated again by centrifugation, and then 20 mL of N,N-dimethylacetamide was added, lightly stirred, and left for one day. N,N-dimethylacetamide and solids were separated by centrifugation, and 19.2 g of N,N-dimethylacetamide solution prepared so that lithium chloride was 8 mass percent was added to the solids, and the mixture was stirred with a stirrer and visually confirmed to be dissolved. The solution in which cellulose was dissolved was filtered through a 0.45 μm filter, and the filtrate was used as a sample for gel permeation chromatography. The apparatus and measurement conditions used are as follows. Equipment: Tosoh HLC-8120 Column: TSKgel SuperAWM-H (6.0mm I.D. x 15cm) x 2 Detector: RI detector Eluent: N,N-dimethylacetamide (lithium chloride 0.2%) Flow rate: 0.6mL / min Calibration curve: Pullulan conversion
[0138] [Average content of alkali-soluble polysaccharides] The alkali-soluble polysaccharide content was calculated by subtracting the α-cellulose content from the holocellulose content (Wise method) according to the method described in the non-patent literature (Wood Science Experiment Manual, edited by the Japan Wood Research Society, pp. 92-97, 2000) for cellulose fibers. The alkali-soluble polysaccharide content was calculated three times for each sample, and the number average of the calculated alkali-soluble polysaccharide contents was taken as the average alkali-soluble polysaccharide content of the cellulose fibers.
[0139] <Fibrous material (aramid fiber PA-Fiber)> As a commercially available aramid fiber, Tiara KY400S manufactured by Daicel FineChem was used. ≪Wood flour≫ Cedar wood was crushed to about 2 to 5 mm using a cutter mill to obtain wood flour.
[0140] <Thickener> As a commercially available thickener, Acofloc N-104 made of polyacrylamide MT Aquapolymer Sodium carboxymethylcellulose manufactured by Tokyo Chemical Industry Co., Ltd. Hydroxypropyl cellulose manufactured by Tokyo Chemical Industry Co., Ltd. Hydroxyethyl cellulose manufactured by Tokyo Chemical Industry Co., Ltd. Polyacrylic acid Fujifilm Wako Pure Chemical Industries, Ltd. Polyvinyl alcohol manufactured by Tokyo Chemical Industry Co., Ltd. N-Vinylacetamide Tokyo Chemical Industry Co., Ltd. Polyethylene oxide: Alcox E-300 manufactured by Meisei Chemical Propylene glycol manufactured by Tokyo Chemical Industry Co., Ltd. Soluble starch (Nacalai Tesque) Guar gum manufactured by Tokyo Chemical Industry Co., Ltd. Gellan gum made by Nacalai Tesque Gelatin made by Nacalai Tesque Sodium alginate (manufactured by Nacalai Tesque) was used.
[0141] <<Particulate component>> As a commercially available particulate component, spherical silica Snowtex (hydrophilic, 50 nm) manufactured by Nissan Chemical was used.
[0142] <Surfactants> The commercially available surfactants used were PEG-PPG GL-3000 manufactured by Sanyo Chemical Industries, Ltd. and hydrogenated castor oil ether RCW-20 manufactured by Aoki Oil & Fat Co., Ltd.
[0143] <Preparation and evaluation of fibrous material dispersion> The obtained fibrous material, distilled water, the above-mentioned commercially available thickener, particulate component, and surfactant were mixed in the ratios shown in Tables 1 and 2, and then the mixture was stirred for 1 hour with a stirring blade rotating at 300 rpm to prepare a fibrous material dispersion.
[0144] [Subsidence degree α] Distilled water was added to the obtained fibrous material dispersion so that the fibrous material was 0.05% by mass to prepare a test dispersion. 20 ml of the test dispersion was dispensed into a 30 ml glass vial, and then dispersed with a homogenizer (10,000 rpm, 1 minute). Then, 8 ml of the test dispersion was quickly placed in a 15 ml screw-top test tube (12 mm inner diameter), sealed, and manually shaken to make the dispersion uniform. The transmittance (hereinafter also referred to as initial transmittance) of the dispersion at a wavelength of 850 nm was measured using a liquid dispersion stability evaluation device Turbiscan (manufactured by FORMULACTION). In addition, after leaving this test tube at 23° C. for 24 hours, the height from the bottom of the dispersion to the separation interface and the height from the bottom of the dispersion to the top of the dispersion were measured using the liquid dispersion stability evaluation device, with the height at which the transmittance becomes 50% at the above wavelength being defined as the separation interface, and the following formula (1): α = 1 − ([A] / [B]) (1) (In formula (1), [A] is the height from the bottom of the dispersion to the separation interface, and [B] is the height from the bottom of the dispersion to the top of the dispersion.) The degree of settling α was determined according to the above. When the height at which the above-mentioned permeability becomes 50% was not defined, the region with a higher permeability than the above-mentioned initial permeability was defined as the supernatant portion, and the region with a lower permeability was defined as the sediment portion, and the boundary between the supernatant portion and the volume portion was defined as the separation interface, and the degree of settling α was determined according to the above (1). The smaller the degree of settling α, the better the stability as a fibrous material dispersion, the better the supply stability with a pump described later, and the better the handling when transferring the dispersion, which is industrially useful. In addition, the smaller the degree of settling α, the better the dispersibility of the fibrous material, and therefore the better the mechanical properties (especially tensile elongation and tensile strength) of the resin composition.
[0145] [Dispersibility] After thoroughly stirring the fibrous material dispersion, one drop (approximately 0.3 mL) was placed on a glass slide and then sandwiched between two glass slides at a force of 0.05 MPa to simulate squeezing inside a pipe. Dispersibility was evaluated based on the number of aggregates with a diameter (i.e., maximum diameter length) of 1 mm or more observed in this way. A...0 pieces B...1 piece C...2~10 pieces D...11 or more
[0146] [Supply volume and concentration stability] A tube pump with an inner diameter of 5 mm was used to transfer the fibrous material dispersion to a resin pipe with a diameter of 10 mm, with the transfer conditions being a rotation speed that transferred distilled water at 150 g / min. The discharged product was collected in a container, and its concentration and supply rate (g / min) were measured every minute. The supply rate stability and concentration stability were evaluated according to the following criteria. (Supply amount stability) A: The pump does not clog during 30 minutes of operation, and the standard deviation of the supply volume is within 5%. B: The pump is not clogged during 30 minutes of operation, and the standard deviation of the supply volume is between 5% and 10%. C: The pump clogs after 5 to 30 minutes of operation, or the standard deviation of the supply volume is between 10% and 50%. D: The pump becomes clogged and becomes inoperable in less than 5 minutes. (concentration stability) A: Standard deviation of concentration is within 5% B: Standard deviation of concentration is more than 5% and less than 10% C: Standard deviation of concentration is more than 10% and less than 30% D: Standard deviation of concentration is more than 30%
[0147] <Preparation and evaluation of resin composition> The fibrous material dispersion was stirred in a planetary mixer (Primix Corporation, product name "Hivismix 2P-1") at 50 rpm for 10 minutes at 25°C and atmospheric pressure, and then dried under reduced pressure at 50 rpm for 8 hours under reduced pressure conditions of a jacket temperature of 80°C and -0.1 MPa to obtain a dried fibrous material.
[0148] The obtained fibrous material and thermoplastic resin were melt-kneaded under the following conditions in the ratios shown in Tables 1 and 2 using a twin-screw extruder with 13 cylinder blocks (OMEGA30H, manufactured by STEER, L / D=60) to obtain pellets of fibrous material reinforced thermoplastic resin. (Melting and kneading conditions) Rotation speed: 300 rpm Cylinder temperature: 250°C (for all except Example 35 and Comparative Example 15) or 200°C (for Example 35 and Comparative Example 15)
[0149] [Tensile yield strength, tensile elongation at yield (TEy), tensile elongation at break (TEb)] Multipurpose test pieces conforming to ISO294-3 were molded using an injection molding machine with a maximum clamping pressure of 75 tons, and tests were conducted under conditions conforming to JIS K6920-2 with n=10. Note that since polyamide resin changes due to moisture absorption, it was stored in an aluminum moisture-proof bag immediately after molding to suppress moisture absorption. The ratio of the tensile elongation at yield (TEy) to the tensile elongation at break (TEb) [TEb / TEy] was calculated.
[0150] As is clear from Tables 1 and 2, the fibrous material dispersions obtained in Examples 1 to 28 were fibrous material dispersions containing a thickener and the fibrous material was highly dispersed, so that in addition to dispersibility, they had excellent stability of the supply amount and supply concentration during pump transfer. On the other hand, the fibrous material dispersions of Comparative Examples 1 to 8 were not stable in the supply amount and concentration during transfer even when the fibrous material concentration was low, causing clogging in the pump, and when the fibrous material concentration became high, it became impossible to transfer the liquid.
[0151] As is clear from Table 3, the fibrous-substance-reinforced thermoplastic resins obtained in Examples 29 to 40 had excellent tensile strength and tensile elongation because the aggregation of the fibrous material was suppressed and the fibrous material was highly dispersed due to the water retention effect of the thickener. On the other hand, the fibrous-substance-reinforced thermoplastic resins of Comparative Examples 9 to 15 had tensile strength and tensile elongation inferior to those of the Examples because the dispersion of the fibrous material was insufficient.
[0152] [Table 1]
[0153] [Table 2]
[0154] [Table 3] [Industrial Applicability]
[0155] The fibrous material dispersion of the present disclosure can impart high strength to resin molded articles due to the high degree of dispersion of the fibrous material, and therefore can be suitably used in fields such as automotive interior and exterior material applications.
Claims
[Claim 1] 100 parts by weight of a dispersion medium; 0.01 to 20 parts by mass of a fibrous material dispersed in the dispersion medium; A fibrous material dispersion comprising: the fibrous material is cellulose fiber, The test dispersion prepared from the fibrous material dispersion had a molecular weight of 1: α=1-([A] / [B])...(1) (In formula (1), [A] is the height from the bottom surface of the dispersion to the separation interface, and [B] is the height from the bottom surface of the dispersion to the top surface of the dispersion.) The sedimentation degree α calculated according to the following formula is 80% or less, The test dispersion is the fibrous material dispersion itself when the concentration of the fibrous material in the fibrous material dispersion is 0.05 mass%, and when the concentration is not 0.05 mass%, the test dispersion is a fibrous material dispersion prepared by concentrating the fibrous material dispersion or diluting it with the same dispersion medium as the dispersion medium so that the concentration is 0.05 mass%.
Citation Information
Patent Citations
Food containing cellulose nanofiber, and method for producing the same
JP2013236585A
Cold insulating implement
JP2014133826A
Thickner composition
JP2014141675A
Pulp content resin molded article and producing method thereof
JP2016069543A